2019
DOI: 10.3146/ps18-4.1
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation and components of peanut rust resistance of newly developed breeding lines

Abstract: Field, greenhouse, and growth chamber experiments were conducted to determine the level of resistance to Puccinia arachidis Speg. in newly developed breeding lines of peanut (Arachis hypogaea L.). These lines were developed in the UF150 project of the Peanut Collaborative Research and Support Program (Peanut CRSP) as part of the United States Agency for International Development (USAID). Field experiments were carried out in Citra, FL and Tifton, GA from 2010 to 2013. Five genotypes Tifrust-10 and Tifrust-13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Defoliation reduces healthy leaf area and affects the rate of photosynthesis and weakens the stems and pegs causing pods to fall off during up-rooting. If the leaf spot is not controlled in initial stage of disease development, defoliation level exceeds 50 percent and yield loss also exceeds 50 percent or more [ 36 ]. In the present study, we found genes responsible for senescence showing downregulation in susceptible genotypes (TAG 24) as compared to resistant genotype (GPBD 4) ( Table S18; Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Defoliation reduces healthy leaf area and affects the rate of photosynthesis and weakens the stems and pegs causing pods to fall off during up-rooting. If the leaf spot is not controlled in initial stage of disease development, defoliation level exceeds 50 percent and yield loss also exceeds 50 percent or more [ 36 ]. In the present study, we found genes responsible for senescence showing downregulation in susceptible genotypes (TAG 24) as compared to resistant genotype (GPBD 4) ( Table S18; Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fávero et al (2009) also found sporulation on six accessions of A. stenosperma, two accessions of A. valida, and one accession of A. magna, which were not tested in this study. So far, high resistance to rust has not been identified in A. hypogaea germplasm (Power et al, 2019;Subrahmanyam et al, 1982;Pande and Rao, 2001;Fávero et al, 2009). The lack of high resistance to rust in cultivated germplasm was contributed in part by having a highly susceptible progenitor as well as the ploidy barrier between allotetraploid peanut and its diploid, highly resistant Arachis relatives.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation to breeding rust-resistant cultivars is that only moderate levels of resistance have been identified in A. hypogaea germplasm (Power et al, 2019). Fortunately, high resistance to rust has been identified in numerous wild Arachis species, including the readily U.S.ble A-and B-genome Arachis species, and resistance can be introgressed into cultivated peanut (Subrahmanyam et al, 1982(Subrahmanyam et al, , 1983Pande and Rao, 2001;Fávero et al, 2009).…”
mentioning
confidence: 99%
“…It is controlled in monogenic, digenic and trigenic manners (Daudi et al, 2021a). Further, resistance to rust has been identified in wild relatives, elite inbred lines, recently developed breeding lines and commercial cultivars (Pande and Rao, 2001, Favero et al, 2015, Sudini et al, 2015, Han et al, 2018, Power et al, 2019. However, there is limited understanding on the histopathological differences among the genotypes that might have led to the visual differences in signs and symptoms including lesion and sporulation levels.…”
Section: Introductionmentioning
confidence: 99%